Relationship between contact with LGBT individuals and acceptance of LGBT in Malaysia - Ting, Su Hie; Ling, Hsin Nie (2022)
: Contact with LGBT individuals may result in more favourable attitudes towards homosexuality and research has suggested that the people who are more open to gender non-conformity may be young, female and non-religiously affiliated. However, the degree of acceptance towards LGBT has not been thoroughly investigated. The study examined the relationship between contact with LGBT individuals and acceptance of LGBT in Malaysia. The specific aspects studied are: (1) level of intergroup contact with LGBT individuals; (2) degree of acceptance towards LGBT individuals; and (3) relationship between intergroup contact and acceptance towards LGBT individuals. The questionnaire data were from 413 Malaysian respondents from various age, ethnic, and religious backgrounds. The results showed that about half of respondents have direct contact with LGBT individuals as in having close friends who are LGBT or knowing a LGBT couple but very few have attended a marriage ceremony for LGBT couples, are in a romantic relationship with LGBT individuals or are LGBT themselves. A majority of the respondents know the challenges of LGBT individuals through reading about them but few have taken active steps to express support for LGBT. The respondents can accept it if they found out their friends, neighbours, colleagues, educators and close relatives are LGBT but are not as tolerant if their child or religious leader is LGBT. The acceptance of LGBT individuals is significantly correlated with the level of intergroup contact with LGBT individuals.